PENGARUH EKSTRAK DAUN COCOR BEBEK (BRYOPHYLLUM PINNATUM) TERHADAP MORTALITAS LARVA NYAMUK - Manao, Ildefonsus Jefri (Jurnal Sapta Agrica, 2024)
The aim of this research was to determine the effect of cocorbek (Bryophyllum pinnatum) leaf extract on mosquito larvae mortality. The research method uses a type of quantitative research with a true experimental approach (pure experiment). It is said to be true experimental because here the researcher intervenes by manipulating the independent variables used as factors, and to see the effects they cause. Researchers will closely observe all other factors that may be considered to influence, suppress and interfere with the results of the experiment. The research results were based on hypothesis testing using one way ANOVA analysis and the results obtained were an Fcount value of 34.536 and a sig value of 0.000. With the hypothesis that Fcount > Ftable and it is said to be significant if the sig value < 0.05. So if compared with Ftable in this study which is 2.77, then Fcount is 34.536 > Ftable 2.77. So Ha is accepted (there is an effect of cocorbek leaf extract on mosquito larvae mortality) and Ho is rejected (there is no effect of cocorbek leaf extract on mosquito larvae mortality). The conclusion of the research is that cocorbek leaf extract has an effect on the mortality of mosquito larvae. In treatment P0, it showed that no mortality occurred because cocorbek leaf extract was not given. Treatment P1 given cocorbek leaf extract had the lowest average mortality value. Meanwhile, P5 treatment had the highest average mortality value. This shows that the higher the concentration of Cocor Bebek leaf extract given, the more mosquito larvae will die. Cocorbek leaf extract can affect the mortality of mosquito larvae because it contains active chemicals that can inhibit larval growth, such as alkoloids, flavonoids, saponins and tannins which are toxic to mosquito larvae.